MOTIVASI KERJA KARYAWAN HOUSEKEEPING DI HOTEL COMFORT KOTA DUMAI PROVINSI RIAU - N.K Swastika Ratri Arini; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research is about work motivation of housekeeping employees in Comfort Hotel City Dumai. This study aims to find out how the motivation of employee housekeeping work at Comfort Hotel Dumai City Province. The sample in this study amounted to 20 people by using the sample population technique. This study uses quantitative descriptive method to classify the data and then compiled by using the frequency and see the mode. And for data collection techniques in this study using questionnaires. By using Likert scale as a measuring tool. Based on the results of research obtained on employee motivation housekeeping in Comfort Hotel Dumai City Riau Province is less agree / less motivated. This is evidenced by the total overall average gain from internal and external factors is 3 points.Keywords: motivation, intern factor, ekstern factor